Kompetensi Absolut Peradilan Agama Dalam Mengadili Perkara Yang Di Dalamnya Terdapat Sengketa Hak Milik Dikaitkan Dengan Asas Personalitas Keislaman - Roni Satriya Cahyadi; Harjono, S.H., M.H - (Sebelas Maret University, 2017)
This Legal research is to determine the limits of the competence of the Religious Courts adjudicate on property right disputes associated with the principles of Islamic personality, as well as its application in the Supreme Court Decision No. 001-SKM / MA / 2015. This is prescriptive normative research. The approach used case approach and statute approach with the primary law and secondary law sources. The primary law sources are the law no. 3 of 2006 and the Supreme Court Decision No. 001-SKM / MA / 2015, and secondary law sources are books, law journals and other article documents related to the competence of the Religious Courts on property right disputes. Based on Article 50 of Law No. 3 of 2006 on the Religious Courts, the competency of Religious Court are property right disputes among Muslim, the dispute has samilar object with the competency of Religious Court, and case of property right disputes with proceedings ini Religious Court are not independent or interrelated cases one another. The implementation in the case that implied in Supreme Court decision number 001-SKM / MA / 2015 about dispute adjudicate competency between District Court of Limboto against Religious Court of Limboto regarding similar object which is a property right dispute on District Court in case of marital property distribution on Religious court, which is in the decision concluded that property right dispute along with marital property distribution is settled by Religious Court in one verdict. Keywords : Religious Courts, Property Right, Islamic Personality